2009
DOI: 10.4064/sm193-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Maps preserving zero products

Abstract: Abstract. A linear map T from a Banach algebra A into another B preserves zero products if T (a)T (b) = 0 whenever a, b ∈ A are such that ab = 0. This paper is mainly concerned with the question of whether every continuous linear surjective map T : A → B that preserves zero products is a weighted homomorphism. We show that this is indeed the case for a large class of Banach algebras which includes group algebras.Our method involves continuous bilinear maps φ : A × A → X (for some Banach space X) with the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
153
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 28 publications
2
153
0
Order By: Relevance
“…The author would like to thank Armando R. Villena for providing the preprints of the manuscripts [1], [2], and [3]. The author also would like to thank the referee for carefully reading this article and providing helpful comments.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The author would like to thank Armando R. Villena for providing the preprints of the manuscripts [1], [2], and [3]. The author also would like to thank the referee for carefully reading this article and providing helpful comments.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In [1], it is shown that L 1 (G) always has property (B). In Section 3, we combine their result together with our results in Section 2 and the structure of groups with polynomial growth to show that the space of bounded n-cocycles from L 1 (G)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our first result is an easy consequence of Lemma 3.5 and a deeper result from [1]. From now on we will consider the norm inequality condition (N), which, as observed in the introduction, follows immediately from the spectral inclusion condition (S) if a and b are selfadjoint.…”
mentioning
confidence: 97%
“…For more studies concerning Jordan derivations we refer the reader to [5,8,10,12,16,17,18,19] and the references therein. Also, there have been a number of papers concerning the study of conditions under which (generalized or Jordan) derivations of rings can be completely determined by the action on some sets of points [1,2,3,7,9,13,14,15,21,22].…”
Section: Introductionmentioning
confidence: 99%